(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The object of this article is the methodology of psycholinguistics concerning analyzing concepts. The article’s relevance is due to the need to apply new approaches to linguistic phenomena analysis, for which a purely linguistic methodology is not enough. The compilation method, a comparative method, and a linguistic modeling method are utilized to fulfill the study’s aim. The author describes in detail the research gaps that exist at the moment in psycholinguistics, in particular, the structure of the relationship between sensory, short-term and long-term memory is still not fully defined, and therefore the basis for a deep analysis of conceptualization is not fully clear. The author concludes that the psycholinguistic methodology has the greatest explanatory power concerning the cognitive process of conceptualization. At the same time, in the case of comparative analysis of various linguistic cultures, the need for additional use of the conceptual and methodological apparatus of cultural studies and ethnology is actualized.